Meningkatkan Pemahaman Siswa Tentang Penjumlahan Dan Pengurangan Bilangan 0 Sampai 500 Melalui Metode Demonstrasi Pada Siswa Kelas II Di Mi Tarbiyatul Ulum Kecamatan Menganti Gresik - Ria Resti Fauziah; Arinil Haq Al Azkiya' (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2022)
This study aims to determine whether or not the discovery learning method has an influence on learning outcomes and students' scientific attitudes in the natural sciences subject matter of the properties of light for class V and to determine student responses to the learning process using discovery learning methods. This research was conducted at SDN Menganti. The research method used was quasi-experimental with nonequivalent control group design and sampling using saturated sampling technique. The research sample consisted of 30 VA class students as the experimental class and 30 VB class students as the control class. The research instrument used was the instrument of learning outcomes and scientific attitudes and the results were tested using the t-test. From the results of the calculation of the t test for learning outcomes, the tcount value is 3.95 while the ttable value is 2 as well as the scientific attitude t test calculation obtained a tcount value of 7.05 while the ttable value is 2 at a significance level of α 0.05 with the determination of –ttable ≤ tcount ≤ ttable. Then Ha is accepted. So it can be concluded that there is an influence of the discovery learning method on learning outcomes and scientific attitudes in class V science subjects.